Moraceae del Peru - Reynel Rodriguez, Carlos (2025)
The botanical family Moraceae, which includes important and well-known species such as the Mulberry (Morus alba, Morus nigra), the Fig tree (Ficus carica) and the Breadfruit tree (Artocarpus altilis, Artocarpus heterophyllus), has a large number of wild representatives in our territory; in fact, it is usually the second most abundant arboreal group in the tropical rainforests of Peru, after the Leguminosae. The genus Ficus, with more than 60 native peruvian species, has been already treated in Flora Ilustrada Peruana (Reynel, 2024). The present treatment complements it, presenting the native (70 species) and cultivated (5 species: Artocarpus altilis, Artocarpus heterophyllus, Castilla elastica, Morus alba, Morus nigra) of Moraceae of the country. They are mostly distributed in the lowland Amazonian humid forests, with an exclusive endemic species from Peru (Perebea longepedunculata), six endemic taxa between Peru-Ecuador (Dorstenia umbricola, Perebea guianensis subsp. pseudopeltata, Pseudolmedia gentryi y Sorocea sprucei subsp. subumbellata), one between Peru-Bolivia (Dorstenia peruviana), and one between PeruBrazil (Naucleopsis riparia). A good percentage of the species have fruits edible for humans; several have valuable timber; others play an essential role in providing food for the maintenance of wildlife in forests and natural environments. In the same tenor of previous publications in this series, the existing species are shown including detailed descriptions and illustrations, as well as their updated nomenclature, and information on their distribution and uses, with information based upon examination of more than 1200 botanical specimens.